2014
DOI: 10.1111/bjd.13214
|View full text |Cite
|
Sign up to set email alerts
|

The dysfunctional innate immune response triggered by Toll-like receptor activation is restored by TLR7/TLR8 and TLR9 ligands in cutaneous lichen planus

Abstract: These findings point to a defect in the TLR signalling pathways in cutaneous LP. Agonists of TLR7/TLR8 or TLR9 overcame impaired IFN-α secretion in LP, strategically acting as adjuvants to improve the type I response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
1
27
0
2
Order By: Relevance
“…TLR8 agonist may overcome the inhibitory function of adenosine/cAMP avoiding fully dendritic cells activation [28]. Thus, the adjuvant effect of CL097 must be further evaluated, although our previous reports also demonstrated improvement in cytokine production induced by CL097 in cutaneous diseases, such as lichen planus [29], and during HIV infection [30]. …”
Section: Discussionmentioning
confidence: 99%
“…TLR8 agonist may overcome the inhibitory function of adenosine/cAMP avoiding fully dendritic cells activation [28]. Thus, the adjuvant effect of CL097 must be further evaluated, although our previous reports also demonstrated improvement in cytokine production induced by CL097 in cutaneous diseases, such as lichen planus [29], and during HIV infection [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Because TLR agonists mimic PAMPs as viral components, the use of synthetic TLR agonists is an interesting approach because of the possible viral aetiology of LP. We previously demonstrated that a dual TLR7/TLR8 agonist is a potent adjuvant for inducing cytokines, including proinflammatory and regulatory cytokines, and for restoring type I IFN in other diseases . TLR7 and TLR8 interact with MyD88: TLR8 leads to nuclear factor‐κB activation, whereas TLR7 interacts with IL‐1 receptor‐associated kinase (IRAK)1/4, tumour necrosis factor receptor‐associated factor (TRAF)3 and TRAF6 to activate IFN regulatory factor (IRF) family members .…”
Section: Discussionmentioning
confidence: 99%
“…LP has been associated with certain viral infections, and factors such as DAMPs and PAMPs may also contribute to the inflammatory response of the disease. The involvement of PAMPs/DAMPs has been described in LP, including differential expression of Toll‐like receptor (TLR)2 and TLR4 in oral epithelial cells from oral (O)LP; defects in the TLR signalling pathways in peripheral blood mononuclear cells (PBMCs) in cutaneous LP, such as impaired interferon (IFN)‐α secretion that can be ameliorated by agonists of TLR7/TLR8 or TLR9; DAMP High mobility group box 1 protein (HMGB1)‐mediated proinflammatory conditions via the Receptor for advanced glycation end products (RAGE) and TLR4 signalling axes in OLP; and upregulation of HMGB1 and TLR4 in skin lesions of LP . Moreover, skin lesions of LP exhibit increased NLRP3 mRNA expression, upregulation of interferon‐inducible genes, and low levels of human endogenous retrovirus .…”
Section: Introductionmentioning
confidence: 99%
“…One study in cutaneous LP patients evaluated the effects of different TLR agonists on peripheral blood mononuclear cells and reported an increase in TNF-a through TLRs 2, 4, 5 and decrease in TNF-a through TLRs 3 and 7. Stimulation of cells with TLRs 7/8 and 9 agonists as adjuvants increased IFN-a production [59].…”
Section: Lichen Planusmentioning
confidence: 97%